Ceres- GO healthcare services: creation, evolution, functionality and regional polarization - Freitas, Wagner Abadio de; Araújo Sobrinho , Fernando Luiz (Revista Cerrados, 2022)
Social and regional interections are results of a long and short period of time. Due Ceres is located in a central area, since the creation of the city, when the National Agricultural Colony was established in the region, it has a regional importance. According to the increasing of economy, Ceres became reference in the healthcare services not just in the region but in all the state. Insertion of technical objects and equipaments had permitted an emergence of an urban area linked with all the cities around, these counties depends of the medical services offered by Ceres. Thus the importance of study and know more about the urban system and its polarization. It´s a different view for a same space. This search aim shows considerations about Ceres centrality, polarization, development based in theoretical references and empirical research and demonstrates the functional importance of the neighbooring cities dependency of Ceres healthcare services.